Standar Kompetensi Lulusan dan Kompetensi Inti pada Kurikulum 2013 di Madrasah Ibtidaiyah - Suradi, Ahmad; Andrea, Cecen; Anita, Putri Surya; Putri, Indira Agleo; Fitriani, Depi; Sari, Intan Wulan (Awwaliyah: Jurnal Pendidikan Guru Madrasah Ibtidaiyah, 2022)
Graduate competency standards have a fundamental role in regulating the curriculum each year, graduate competency is calculated from the thinking capacity and expertise of each student which aims to evaluate their affective and psychomotor abilities. These graduate competency standards are known in the school environment as a curriculum. The curriculum is a component that must be lived by each student, if the student cannot complete every curriculum in his school, the child cannot be declared graduated. Madrasah Ibtidaiyah core competencies are skill levels in achieving graduate competency standards that must be possessed by SD/MI students at each grade level. These competencies are made for certain classes, through these core competencies, cross-coordination in the initial competencies in the learning of each class can be monitored. The target of the 2013 curriculum is stated in the graduate competency standards. Meanwhile, the targets of the 2013 curriculum are listed in the content standards as a cluster of graduate competency standards, which consist of basic competencies and core competencies.